2020
DOI: 10.1002/anie.202005207
|View full text |Cite
|
Sign up to set email alerts
|

Tighter Confinement Increases Selectivity of d‐Glucose Isomerization Toward l‐Sorbose in Titanium Zeolites

Abstract: Aqueous-phase isomerization of d-glucose to d-fructose and l-sorbose is catalyzed in parallel by Lewis acidic Ti sites in siliceous frameworks.G lucose isomerization rates (per Ti,3 73 K) are undetectable when Ti sites are confined within mesoporous voids (Ti-MCM-41, TiO 2-SiO 2) and increase to detectable values when Ti sites are confined within the smaller 12-membered ring (12-MR) micropores of Ti-Beta. Isomerization rates decrease to lower values (by % 20)with further decreases in micropore sizeasT isites a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…124,125 Glc has a Stokes diameter of 0.72 nm; 126 however, due to flexibility of this molecule, it can diffuse into MFI and Beta zeolites with nominal pore diameters of 0.55 and 0.7 nm, respectively. 127 Though the confinement effect can potentially influence isomerization performance, 127 no such effects have been reported for zeolites with basic sites yet. Interestingly, utilization of hierarchical zeolites results in an improved isomerization rate.…”
Section: Isomerization In the Presence Of Solid Catalystsmentioning
confidence: 99%
See 2 more Smart Citations
“…124,125 Glc has a Stokes diameter of 0.72 nm; 126 however, due to flexibility of this molecule, it can diffuse into MFI and Beta zeolites with nominal pore diameters of 0.55 and 0.7 nm, respectively. 127 Though the confinement effect can potentially influence isomerization performance, 127 no such effects have been reported for zeolites with basic sites yet. Interestingly, utilization of hierarchical zeolites results in an improved isomerization rate.…”
Section: Isomerization In the Presence Of Solid Catalystsmentioning
confidence: 99%
“…In recent years, an interest toward utilization of some classes of solid bases, such as zeolites, supported amines, and Mg–Al hydrotalcites has increased. Catalytic activity of zeolites in Na + , K + , Mg 2+ , or Ca 2+ forms was reported; ,, in addition, MgO supported on zeolites was tested. , Glc has a Stokes diameter of 0.72 nm; however, due to flexibility of this molecule, it can diffuse into MFI and Beta zeolites with nominal pore diameters of 0.55 and 0.7 nm, respectively . Though the confinement effect can potentially influence isomerization performance, no such effects have been reported for zeolites with basic sites yet.…”
Section: Isomerization In the Presence Of Solid Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another example is the work of Gounder and co-workers, who studied the conversion of glucose to sorbose, the precursor to synthetic ascorbic acid. 62 The process can be catalyzed by Lewis acids, so the authors screened Ti-modified zeolites, mesoporous silica, and non-porous silica as catalysts. The mechanism (Scheme 3) involves the adsorption of glucose to the Ti site at the O5 position, followed by ring-opening to the open-chain form followed by coordination of the carbonyl in the C1 position to the Ti site.…”
Section: Confinement In Pores and Cavitiesmentioning
confidence: 99%
“…Tetravalent metal ions (Ti 4+ , Ge 4+ , Zr 4+ , Sn 4+ ) can be incorporated into the zeolite by means of isomorphous substitution to introduce the well-defined Lewis acid center for the zeolite, which can enhance the catalytic activity of the zeolite for a designated reaction. Mal et al reported Sn-ZSM-12 zeolite with a Si/Sn >70 that could be used as an effective catalyst for the oxidation of phenol, m -cresol, and m -xylene, which performed better than the Sn-free ZSM-12. They also found that Sn-ZSM-12 exhibited better activity than mesoporous Sn-MFI/MEL in the oxidation of naphthalene and 2-methylnaphthalene to naphthol, 2-naphthalenemethanol and 2-naphthaldehyde .…”
Section: Introductionmentioning
confidence: 99%